Characterisation of calcium carbonate and its polymorphs from cockle shells (Anadara granosa) - Kh. Nurul Islam; Md Zuki, Abu Bakar; Mustapha, M. Noordin; Mohd Zobir, Hussein; Norshazlirah Shazlyn, Abd Rahman; Md. Eaqub, Ali (Elsevier B.V., 2011)
Link to publisher's homepage at http://www.elsevier.com/wps/find/homepage.cws_home